Hazard Identification, Risk Assessment and Risk Control (HIRARC) pada CV Lisa Jaya Mandiri Food - Michael Timothy (Jurnal Titra, 2022)
CV Lisa Jaya Mandiri Food is a company engaged in the production and distribution of food with famous products they have AMDK with AMPO trademark. This final project is conducted by interview method with the head of production company and workers as well as direct observation in the field. This final project aims to help companies know the potential dangers of existing activities, assess the potential dangers and determine ways to overcome them. From the analysis of the final project, obtained 15 activities that have the potential to cause work accidents. Of the 15 activities, the severity caused was in the moderate, significant and high categories. There are 22 proposed Risk Control which is dominated by the control of administrative engineering methods and PPE. The author's control proposal has been approved by the company. After the proposed control is given, it is predicted that the risk rating for all sub-activities is in the low category.